KEBIJAKAN PEMBERIAN NIK DALAM KTP TERHADAP STATUS KEPENDUDUKAN DAN KEWARGANEGARAAN - Sutiyani Sutiyani (Legal Spirit, 2017)
On the basis of the the provisions of law, ID Number , and IDs of Indonesian population and all personal information or data collected shall be maintained by the organizing authority. The personal data protection will be used to secure the citizens’ rights against any misuse of personal data of the population including Family Head, Pasword, date / month / year of birth, informationon physical/ mental records, personal data and other important information thatshould to be protected. Population data generated by the information system and stored in the population database can be utilized for various purposes, such as materials analysis and formulating development planning, knowledge assessment, implementation of data on voters in elections. Keywords: ID Card, ID Number, Population and Citizenship Status.